Fuzzy Logic Based Battery Control System Design for Electric Vehicles - Cetin, Muhammed Sefa; Guler, Hasan; Gencoglu, Muhsin Tunay (Institute of Electrical and Electronics Engineers Inc., 2021)
Electric vehicles have emerged as a solution to the environmental problems caused by conventional internal combustion engine vehicles. In spite of the intensified studies in recent years, the use of electric vehicles is not at the desired level. The most important reason for this is the battery groups. Therefore, studies on electric vehicles focus on the battery parameter. Disadvantages of batteries; high production costs, battery charging time and full charging range of the battery. In this study, a control system is designed to increase the range of the electric vehicle by prolonging the discharge time of the battery. Fuzzy Logic method was used while designing the control system. In addition, 100 scenarios were produced using Monte-Carlo simulation and Gaussian Distribution method and the accuracy of the operation of the system was examined. © 2021 IEEE.
2021 Innovations in Intelligent Systems and Applications Conference, ASYU 2021 -- 6 October 2021 through 8 October 2021 -- Elazig -- 174400
Keywords: battery; electric vehicles; fuzzy logic